The Implications of Utilizing Artificial Intelligence-Based Parenting Technology on Children's Mental Health: A Literature Review - Yunike, Yunike; Rehana, Rehana; Misinem, Misinem; Kusumawaty, Ira (Poltekita : Jurnal Ilmu Kesehatan, 2023)
The study aims to look at the development of artificial intelligence to support positive parenting and help improve children's mental health. This research method uses the PRISMA approach through a search process using the keywords "Parenting, Child Mental Health, Artificial Intelligence, Communication, and Discipline Enforcement on the Scopus, Google Scholar, Science Direct, and Pubmed databases in the period 2018 to 2023 with a five-step process to obtain data. After elimination, 1,223 journal articles were obtained that met the inclusion and exclusion criteria of 11 journal articles. Based on the results of the literature review, information was identified regarding the history of the development of artificial intelligence technology, artificial intelligence significantly has a positive impact on children's mental health, through the use of artificial intelligence parents gain meaningful literacy in providing positive care for children. However, the use of artificial intelligence can lead to parents' dependence on artificial intelligence, which is feared to replace human figures. In conclusion, studying the development and adequate use of artificial intelligence technology is urgently needed to improve the ability and quality of parenting to support the optimization of children's mental health.